Регуляризація частково цілочислової задачі векторної оптимізації з квадратичними функціями критеріїв - Лебєдєва, Т.Т.; Семенова, Н.В.; Сергієнко, Т.І. (Доповіді НАН України, 2024)
Представлено нові результати, пов’язані з регуляризацією частково цілочислових задач оптимізації за Парето за умов можливих збурень вхідних даних векторного критерію, який складається з квадратичних функцій. Розроблена процедура регуляризації ґрунтується на використанні властивості стійкості відносно збурень коефіцієнтів критеріїв векторної задачі оптимізацїі за Слейтером. The article is devoted to the question of regularization of partially integer Pareto-optimization problems with vector criterion input perturbations. New results are obtained for the case when the vector problem is partially integer with quadratic functions as criteria. The developed regularization procedure is based on the use of the Slater stability property with respect to perturbations of criterion coefficients of the vector optimization problem. The obtained results - the conditions of stability to possible perturbations of vector criterion input data and the developed procedure of regularization of vector optimization problems — are related to the solution of problems of correct modeling of economic, ecological, technological, social processes in conditions of effective accounting of incompleteness and uncertainty of input information.